Genetic and environmental relationships among milk yield, persistency of milk yield, somatic cell count and calving interval in Holstein cows - Arash Chegini (Universidad de Antioquia, 2019)
Background: Fertility and health traits, other than production traits, have a major role in the profitability of dairy cattle. Therefore, it seems necessary to include the afore mentioned traits in breeding programs. Hence, genetic parameters are needed to establish breeding plans. Objective: To estimate heritabilities as well as genetic and environmental relationships among total milk yield (TMY), persistency of milk yield (PMY), mean somatic cell count (SCC), mean loge somatic cell count (LnSCC), standard deviation of somatic cell count (stdSCC), and calving interval (CI) using two-trait and multi-trait analyses in Iranian Holstein. Methods: The dataset consisted of 25,883 first lactation records collected from 2002 to 2007 in 97 Holstein dairy herds in Iran. Four criteria of persistency of milk yield (PMY) were calculated using the Wood's gamma function. The WOMBAT1.0 software was used to estimate the (co)variance components using the Average Information Restricted Maximum Likelihood algorithm. Results: Total milk yield (TMY) resulted in the highest heritability estimate (0.29). Heritability estimates for different criteria of persistency of milk yield (PMY) ranged from 0.05 to 0.10. The unfavorable genetic correlation between TMY and calving interval (CI) was 0.71, while that of PMY with CI was 0.46. The estimated environmental correlations were lower than the genetic correlations for all traits, but the trends were generally similar. Conclusion: The results indicate that including PMY in the breeding goals could increase TMY and CI, and decrease somatic cell count (SCC).